(untitled) (Das Questões, 2024)
Four feminists from India, Mexico, and Brazil met in Paris on the occasion of an international symposium on Space Art and Culture – “Global Periphery,” held in September 2022. They sat at a sidewalk café and began imagining the creation of a Space Agency staffed by feminists from the Global South. They discussed topics such as astropolitics, geopolitics, imperialism, multilateralism, economics, Global South, new world order, peripheral knowledge, subaltern knowledge, center and periphery, global periphery, epistemicide, power maps, rulers of the world, rulers of the solar system, futuristic policies, ancestrofuturism, knowledge of indigenous, migratory, and diasporic peoples, diversity, and feminism. The dinner actually took place, but the concepts and conversations in the text do not exactly reproduce the discussions at the dinner; they were developed later, with the author’s poetic license.